P430Antiarrhythmic drug therapy in Russian patients undergoing atrial fibrillation ablation: a sub-analysis of the ESC-EHRA EORP registry. (18th June 2020) - Korobchenko, L; Bayramova, S; Kharats, V; Batalov, R; Silin, I; Kryzhanovskiy, D; Romanov, A; Lebedev, D; Kolunin, G; Zamanov, D; Chetverikov, S; Yashin, S; et al.
Abstract: OnBehalf: EHRA-ESC EORP AFA LT registry Introduction: Despite the effectiveness of atrial fibrillation (AF) catheter ablation (CA), antiarrhythmic therapy (AAT) remains an important part of the complex treatment. Purpose: To analyze AAT dynamics in Russian patients undergoing AF ablation, and to reveal potential factors associated with ongoing AAT in patients without arrhythmia recurrence. Methods: The ESC-EHRA AF ablation registry was conducted in 2012-2016 in EHRA countries. The current analysis included 476 patients (57.1 male; 57.1 ± 8.7 years) who underwent AF ablation in 13 Russian clinics. AAT before, during and at 12-month follow-up (12-FU) was assessed. At baseline, paroxysmal AF was present in 320 (67.2%) patients, persistent AF - in 94 (19.7%), long-standing persistent AF- in 53 (11, 1%), in 9 (1.9%) AF type was unknown. Hypertension (H) was present in 355 (74.6%) patients; congestive heart failure (CHF) (NYHA≥2) in 184 (38.7%) patients; coronary artery disease (CAD) in 132 (27.7%) patients. The CA was the first in 396 (83.2%) cases, redo ablation was performed in 80 (16.8%) cases. AF recurrences were registered according to local clinical practice. Any atrial tachyarrhythmia >30s was considered as a recurrence. Results: A three-month FU (3-FU) visit was performed in 476 (100%) patients, 12-FU - in 390 (81.9%). Prior to PV isolation 439 (92.2%) patients received AAT, while after ablation there was an increase in the number of patients on AAT - 459 (96.4%). The highest number of patients on AAT was detected at 3-FU - 463 (97.3%). During 12 months at least one episode of arrhythmia recurrence was documented in 203 (52.1%) patients, and 370 (94.8%) patients were on AAT at the 12-month visit. After the 12-month visit 307 (78.7%) patients continued to receive AAT, and in 187 (47.9%) of them there was no arrhythmia recurrence after the index ablation. Five (2.7%) of these patients continued a Ic class AAT drug, 35 (18.7%) patients - class III, 129 (69.0%) patients - β-blockers (BB) and 18 (9.6%) patients - calcium channel blockers (CCB). All 187 patients had co-morbidities (75.4% - H; 41.7% - CHF (NYHA≥2; 31.6% - CAD). There were no statistically significant predictors of AAT use in patients without arrhythmia reccurence. According to the univariant regression analysis, the use of AAT III class (mainly-sotalol) at 12 months had a small but statistically significant negative association with left atrial size enlargement (OR = 0.917; 0.860-0.997); class III AAT was negatevely associated with BB therapy (OR = 0.057; 0.016-0.198); CCB therapy was associated with an older age (OR = 1.073; 1.053-1.151). Conclusions: About one-half of patients without apparent arrhythmia recurrence following AF ablation do receive AAT. There were no clinical or procedure-related factors associated with AAT after effective AF ablation. Paradoxically, patients with a smaller left atrial size and without arrhythmia recurrence had more chances to receive class III AAT, what requires further analysis.